A softened membrane model for composite box-girders with corrugated steel webs under pure torsion. (15th October 2018) - Shen, Kongjian; Wan, Shui; Mo, Y.L.; Li, Xiayuan; Song, Aiming
Highlights: A new model is proposed for the behavior of RC/PC composite BGCSWs under pure torsion. The shear strain relations between concrete slabs and CSWs employed in the model is proved to be reasonable. The correction of thickness of shear flow in concrete slabs are considered. The proposed model is able to predict the entire torque-twist curves and is verified by the experimental results. Abstract: The softened membrane model for torsion (SMMT), formerly developed for the torsional analysis of reinforced concrete (RC) members, has the capability of modeling the biaxial strains of concrete with Poisson effect, the tension stiffening effect of concrete and the contribution of concrete in shear. It is extended to the composite box-girders with corrugated steel webs under pure torsion in this study. The extended SMMT for RC composite box-girders with corrugated steel webs incorporates the contribution of corrugated steel webs into the SMMT for RC members by applying the assumption of shear strain relations between concrete slabs and corrugated steel webs. Moreover, the thickness of shear flow zone in concrete slabs is reasonably corrected. Besides, the modifications of equilibrium equations and convergence criteria are conducted for the prestressed concrete (PC) composite box-girders with corrugated steel webs. The modified SMMT for RC/PC composite box-girders with corrugated steel webs is able to predict the overall torsional behavior, including the torque-twist curve and the smeared shear strains in concrete slabs and corrugated steel webs, as well as any other related variables. The accuracy and superiority of the proposed model are verified by comparing the theoretical predictions from the SMMT with the experimental results and the predictions from existing model.